100 Books Every Folk Music Fan Should Own - Weissman, Dick (Rowman & Littlefield Publishers, 2014)
In recent years an almost overwhelming number of books have appeared covering various aspects of American folk music and its history. Before 1970, most comprised collections of songs with a sprinkling of biographical information on noted performers. Over the past decade, however, scholars, journalists, and folk artists themselves have contributed biographies and autobiographies, instructional books and historical surveys, sociological studies and ethnographic analyses of this musical genre. In 100 Books Every Folk Music Fan Should Own, performer and historian Dick Weissman offers a reliable route through the growing sea of book-length studies, establishing for future scholars a foundation for their research. Beginning with early twentieth-century collections of folk songs, the author brings readers to the present by exploring modern studies of important events, critical collections of primary sources, the most significant musical instruction guides, and in-depth portraits of traditional and contemporary American folk musicians. For each title selected, Weissman provides his own brief summary of its contents and assessment of its significance for the reader—whether fan or scholar. Folk music fans, scholars, and students of the American folk music tradition—indeed, any reader seeking guidance on the best books in the field—will want a copy of this vital work.